Seawater corrosion resistant ultrafiltration membrane for water treatment and preparation method thereof
Patent Information
- Application Number
- CN202511173332.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-08-21
- Publication Date
- 2026-10-09
- Estimated Expiration
- 2045-08-21
AI Technical Summary
[0004]为了克服上述的技术问题,本发明的目的在于提供一种耐海水腐蚀的水处理用超滤膜及其制备方法,解决了现有的传统的超滤膜在海水水处理环境中容易受到腐蚀和污染,导致超滤膜性能显著下降,从而增加了水处理成本和运行难度的问题
[0030] A seawater-resistant ultrafiltration membrane for water treatment and its preparation method are disclosed. The method involves mixing carboxyl-containing fluorinated polyarylene ether sulfone material, quaternized zinc-based metal-organic framework material, modified molybdenum disulfide nanoparticles, carboxylated carbon nanotubes, polyvinylpyrrolidone, polyethylene glycol, a crosslinking agent, sodium dodecyl sulfate, and N,N-dimethylacetamide, followed by coating to form a membrane. This ultrafiltration membrane, using carboxyl-containing fluorinated polyarylene ether sulfone material as the main raw material, exhibits good chemical stability and corrosion resistance in seawater environments. It effectively resists the erosion of chloride ions, salts, and other substances in seawater, extending the service life of the ultrafiltration membrane. The addition of quaternized zinc-based metal-organic framework material and its porous structure further enhances its effectiveness. The structure gives the ultrafiltration membrane higher permeability, thereby improving its removal performance. It also endows the ultrafiltration membrane with excellent antibacterial properties, effectively inhibiting biofilm formation, avoiding biofouling, and reducing the cleaning frequency and operating costs. Adding modified nano-molybdenum disulfide powder utilizes its unique layered structure to construct relatively smooth and rigid interlayer nano-confined channels on the membrane surface through ordered stacking and self-assembly. This reduces the adhesion of pollutants in wastewater. Furthermore, its excellent photocatalytic ability enables photocatalytic degradation of pollutants and endows the ultrafiltration membrane with photocatalytic antibacterial capabilities, thereby enhancing its self-cleaning and antifouling abilities. This ensures the long-term removal performance of the ultrafiltration membrane and improves water treatment efficiency.
Smart Images

Figure CN121060338B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of ultrafiltration membranes, specifically to an ultrafiltration membrane for water treatment that is resistant to seawater corrosion and its preparation method. Background Technology
[0002] Ultrafiltration membranes, as an important membrane separation technology, have been widely used in the field of water treatment. However, in seawater treatment environments, due to the large amounts of chloride ions, salt, microorganisms, algae, and organic pollutants in seawater, traditional ultrafiltration membranes are easily corroded and fouled, leading to a significant decline in ultrafiltration membrane performance, thereby increasing water treatment costs and operational difficulties.
[0003] Therefore, developing an ultrafiltration membrane for water treatment that is resistant to seawater corrosion and its preparation method is of great practical significance. Summary of the Invention
[0004] In order to overcome the above-mentioned technical problems, the present invention aims to provide an ultrafiltration membrane for water treatment that is resistant to seawater corrosion and its preparation method. This solves the problem that existing traditional ultrafiltration membranes are easily corroded and contaminated in seawater treatment environments, which leads to a significant decline in the performance of the ultrafiltration membrane, thereby increasing the cost and difficulty of water treatment.
[0005] The objective of this invention can be achieved through the following technical solutions:
[0006] In a first aspect, this application provides an ultrafiltration membrane for water treatment that is resistant to seawater corrosion, comprising the following components in parts by weight:
[0007] The composition includes 17-25 parts of carboxyl-containing fluorinated polyarylether sulfone material, 2-8 parts of quaternized zinc-based metal-organic framework material, 0.8-3.6 parts of modified nano-molybdenum disulfide powder, 0.5-1.7 parts of carboxylated carbon nanotubes, 1-2 parts of polyvinylpyrrolidone, 0.5-0.7 parts of polyethylene glycol, 2-4 parts of crosslinking agent, 0.3-0.5 parts of sodium dodecyl sulfate, and 80-85 parts of N,N-dimethylacetamide.
[0008] The carboxyl-containing fluorinated polyarylene sulfone material is prepared by the following steps:
[0009] Bisphenol AF, 4,4'-difluorodiphenyl sulfone, phenolphthalein, anhydrous potassium carbonate, xylene, and sulfolane were added to a three-necked flask equipped with a stirrer, thermometer, gas delivery tube, and reflux condenser. Nitrogen gas was introduced for protection, and the mixture was stirred for 10-20 min at 20-25℃ and a stirring rate of 200-300 r / min. The temperature was then raised to 120-130℃ and the stirring was continued for 3-4 h. The temperature was then raised to 160-180℃ and the stirring was continued for 5-6 h. After the reaction was completed, the reaction product was cooled to room temperature and then poured into deionized water. The pH was then adjusted to 5-6 with hydrochloric acid solution, and the mixture was allowed to stand. After that, it was vacuum filtered. The filter cake was washed 2-3 times with anhydrous ethanol and distilled water, and then placed in a vacuum drying oven and dried at 60-70℃ for 10-12 h to obtain a carboxyl-containing fluorinated polyarylene ether sulfone material.
[0010] In a preferred embodiment of the present invention, the ratio of bisphenol AF, 4,4'-difluorodiphenyl sulfone, phenolphthalein, anhydrous potassium carbonate, xylene, and sulfolane is 10 mmol: 20 mmol: 10 mmol: 25-30 mmol: 20-25 mL: 50-55 mL; and the mass fraction of the hydrochloric acid solution is 10-15%.
[0011] In a preferred embodiment of the present invention, the quaternized zinc-based metal-organic framework material is prepared by the following steps:
[0012] Step A1: Dimethyl 2-bromomethyl terephthalate, trimethylamine solution, and anhydrous acetonitrile were added to a three-necked flask equipped with a stirrer, thermometer, gas delivery tube, and reflux condenser. Nitrogen gas was introduced for protection, and the reaction was stirred at 20-25℃ and 200-300 r / min for 20-30 min. Then, the temperature was raised to reflux and the reaction was stirred for another 20-30 h. After the reaction was completed, the reaction product was cooled to room temperature, and the solvent was removed by rotary evaporation. The product was then purified by silica gel column chromatography with a mixed solvent to obtain the quaternized dimethyl terephthalate compound.
[0013] Step A2: Add the quaternized dimethyl terephthalate compound, sodium hydroxide solution, anhydrous methanol, and anhydrous tetrahydrofuran to a three-necked flask equipped with a stirrer and thermometer. Stir the reaction at 20-25℃ and 200-300 r / min for 3-5 min. Then, raise the temperature to 100-110℃ and continue stirring for 10-12 h. After the reaction is complete, cool the reaction product to room temperature, remove the solvent by rotary evaporation, pour it into distilled water, adjust the pH to 2-3 with hydrochloric acid solution, and then filter under vacuum. Place the filter cake in a vacuum drying oven and dry it at 40-45℃ for 3-5 h to obtain the quaternized dimethyl terephthalate compound.
[0014] Step A3: Quaternized terephthalic acid compound, zinc nitrate, hydrochloric acid solution, and N,N-dimethylformamide are added to a three-necked flask equipped with a stirrer and thermometer. The mixture is stirred at 20-25℃ and a stirring rate of 200-300 r / min for 10-20 min. Then, the temperature is raised to 90-100℃ and the stirring is continued for 24-48 h. After the reaction is completed, the reaction product is cooled to room temperature and then centrifuged. The precipitate is soaked in anhydrous methanol for 24-48 h, then centrifuged again. The precipitate is placed in a vacuum drying oven and dried at 40-45℃ for 6-8 h to obtain quaternized zinc-based metal-organic framework material.
[0015] In a preferred embodiment of the present invention, the ratio of 2-bromomethyl terephthalate, trimethylamine solution and anhydrous acetonitrile in step A1 is 5g: 25-30mL: 40-50mL.
[0016] In a preferred embodiment of the present invention, the trimethylamine solution in step A1 has a mass fraction of 30-33%; the mixed solvent is a mixture of dichloromethane and anhydrous methanol in a volume ratio of 10-12:1.
[0017] In a preferred embodiment of the present invention, the ratio of the amount of the quaternized dimethyl terephthalate compound, sodium hydroxide solution, anhydrous methanol and anhydrous tetrahydrofuran in step A2 is 3g:30-40mL:20-30mL:10-15mL.
[0018] In a preferred embodiment of the present invention, the molar concentration of the sodium hydroxide solution in step A2 is 3-5 mol / L; and the mass fraction of the hydrochloric acid solution is 25-30%.
[0019] In a preferred embodiment of the present invention, the ratio of the quaternized terephthalic acid compound, zinc nitrate, hydrochloric acid solution and N,N-dimethylformamide used in step A3 is 10 mmol: 10 mmol: 20-25 mL: 50-60 mL.
[0020] In a preferred embodiment of the present invention, the mass fraction of the hydrochloric acid solution in step A3 is 30-35%.
[0021] In a preferred embodiment of the present invention, the modified nano-molybdenum disulfide powder is prepared by the following steps:
[0022] Nano-molybdenum disulfide powder, polyvinylpyrrolidone, and deionized water were added to a three-necked flask equipped with a stirrer and thermometer. The mixture was sonicated at a frequency of 40-50 kHz for 20-30 min. Then, the mixture was stirred at a temperature of 20-25℃ and a stirring rate of 200-300 r / min for 10-20 min. Pyrrole and ferric chloride were then added, and the mixture was heated to 40-45℃ and stirred for another 3-5 h. After the reaction was completed, the product was cooled to room temperature, centrifuged, and the precipitate was washed 2-3 times with ethanol solution. The precipitate was then placed in a vacuum drying oven and dried at a temperature of 60-70℃ for 3-5 h to obtain modified nano-molybdenum disulfide powder.
[0023] In a preferred embodiment of the present invention, the ratio of the amount of nano-molybdenum disulfide powder, polyvinylpyrrolidone, deionized water, pyrrole and ferric chloride is 3g:0.04-0.08g:50-55mL:0.6-1.2g:3-5g.
[0024] In a preferred embodiment of the present invention, the average particle size of the nano-molybdenum disulfide powder is 200 nm; the polyvinylpyrrolidone is PVP-K30; and the volume fraction of the ethanol solution is 40-50%.
[0025] Secondly, this application provides a method for preparing an ultrafiltration membrane for water treatment that is resistant to seawater corrosion, comprising the following steps:
[0026] Step 1: Weigh out 17-25 parts by weight of carboxyl-containing fluorinated polyarylether sulfone material, 2-8 parts by weight of quaternized zinc-based metal-organic framework material, 0.8-3.6 parts by weight of modified nano molybdenum disulfide powder, 0.5-1.7 parts by weight of carboxylated carbon nanotubes, 1-2 parts by weight of polyvinylpyrrolidone, 0.5-0.7 parts by weight of polyethylene glycol, 2-4 parts by weight of crosslinking agent, 0.3-0.5 parts by weight of sodium dodecyl sulfate, and 80-85 parts by weight of N,N-dimethylacetamide, and set aside.
[0027] Step 2: Add carboxyl-containing fluorinated polyarylether sulfone material, quaternized zinc-based metal-organic framework material, modified nano-molybdenum disulfide powder, carboxylated carbon nanotubes, polyvinylpyrrolidone, polyethylene glycol, crosslinking agent, sodium dodecyl sulfate, and N,N-dimethylacetamide to a mixer. Stir and mix for 20-30 minutes at a temperature of 20-25℃ and a stirring rate of 500-700 r / min. Then, raise the temperature to 70-80℃ and continue stirring and mixing for 5-6 hours. After standing for 2-4 hours, pour the mixture onto a smooth glass plate and scrape it with a membrane scraper to form a membrane with a thickness of 100-500 μm. After standing for 2-3 minutes, immerse it in deionized water for 24-72 hours to obtain an ultrafiltration membrane for water treatment that is resistant to seawater corrosion.
[0028] In a preferred embodiment of the present invention, the carboxylated carbon nanotubes are high-purity multi-walled carbon nanotubes TNMC1; the polyvinylpyrrolidone is PVP-K30; the polyethylene glycol is PEG-6000; and the crosslinking agent is silane coupling agent KH-560.
[0029] Compared with the prior art, the beneficial effects of the present invention are:
[0030] A seawater-resistant ultrafiltration membrane for water treatment and its preparation method are disclosed. The method involves mixing carboxyl-containing fluorinated polyarylene ether sulfone material, quaternized zinc-based metal-organic framework material, modified molybdenum disulfide nanoparticles, carboxylated carbon nanotubes, polyvinylpyrrolidone, polyethylene glycol, a crosslinking agent, sodium dodecyl sulfate, and N,N-dimethylacetamide, followed by coating to form a membrane. This ultrafiltration membrane, using carboxyl-containing fluorinated polyarylene ether sulfone material as the main raw material, exhibits good chemical stability and corrosion resistance in seawater environments. It effectively resists the erosion of chloride ions, salts, and other substances in seawater, extending the service life of the ultrafiltration membrane. The addition of quaternized zinc-based metal-organic framework material and its porous structure further enhances its effectiveness. The structure gives the ultrafiltration membrane higher permeability, thereby improving its removal performance. It also endows the ultrafiltration membrane with excellent antibacterial properties, effectively inhibiting biofilm formation, avoiding biofouling, and reducing the cleaning frequency and operating costs. Adding modified nano-molybdenum disulfide powder utilizes its unique layered structure to construct relatively smooth and rigid interlayer nano-confined channels on the membrane surface through ordered stacking and self-assembly. This reduces the adhesion of pollutants in wastewater. Furthermore, its excellent photocatalytic ability enables photocatalytic degradation of pollutants and endows the ultrafiltration membrane with photocatalytic antibacterial capabilities, thereby enhancing its self-cleaning and antifouling abilities. This ensures the long-term removal performance of the ultrafiltration membrane and improves water treatment efficiency.
[0031] In the preparation of ultrafiltration membranes, a carboxyl-based fluorinated polyarylene ether sulfone material was first prepared. This material was polymerized using bisphenol AF, 4,4'-difluorodiphenyl sulfone, and phenolphthalein as monomers. The molecular structure of this material contains a large number of fluorinated groups, forming a chemically inert barrier that prevents the penetration of corrosive media and improves its resistance to seawater corrosion. Furthermore, the presence of numerous carboxyl groups allows it to react with the epoxy groups on the silane coupling agent KH-560 to form a cross-linked network, further enhancing its resistance to seawater corrosion. Simultaneously, the abundant carboxyl groups endow it with strong hydrophilicity, enabling it to bind with water molecules through hydrogen bonds, thereby forming a stable hydration layer and reducing the adsorption of organic matter and microorganisms in seawater.
[0032] In the process of preparing the ultrafiltration membrane, a quaternized zinc-based metal-organic framework material was also prepared. This was achieved by reacting 2-bromomethyl terephthalate (DMTB) with trimethylamine, where the bromine atom on DMTB reacts with trimethylamine to form a quaternary ammonium group, yielding a quaternized DMTB compound. Subsequently, the ester group on the quaternized DMTB compound hydrolyzes to form a carboxyl group, yielding a quaternized terephthalic acid compound. Then, the quaternized terephthalic acid compound reacts with zinc nitrate, where the carboxyl group on the quaternized terephthalic acid compound reacts with zinc ions to form the quaternized zinc-based metal-organic framework material. This metal-organic framework material is a porous material with a crystalline structure formed through self-assembly. It can improve the permeability of the ultrafiltration membrane, enhance its removal efficiency and effect, and utilize the quaternary ammonium groups and zinc ions to endow it with excellent antibacterial properties, thereby inhibiting biofilm formation and solving the biofouling problem of ultrafiltration membranes in seawater treatment.
[0033] In the process of preparing the ultrafiltration membrane, a modified molybdenum disulfide nanopowder was also prepared. Using pyrrole as a polymer monomer, polypyrrole was coated on the surface of the molybdenum disulfide nanopowder to obtain the modified molybdenum disulfide nanopowder. After modification, the modified molybdenum disulfide nanopowder can be uniformly dispersed in the ultrafiltration membrane. It not only degrades some of the adsorbed organic matter through photocatalysis, but also enhances the continuity of the hydration layer, thereby giving it excellent antifouling performance. Moreover, polypyrrole also has excellent photocatalytic activity, which can further improve its antifouling performance. Furthermore, the modified molybdenum disulfide nanopowder forms a "tube-sheet heterostructure" with carboxylated carbon nanotubes, shortening the water molecule path, improving the permeability of the ultrafiltration membrane, and enhancing the removal performance of the ultrafiltration membrane. In addition, the carboxylated carbon nanotubes can form hydrogen bond crosslinks with carboxylated fluorinated polyarylene ether sulfone materials and react with the epoxy groups on the silane coupling agent KH-560 to form a crosslinked network, suppressing interface defects. Attached Figure Description
[0034] To facilitate understanding by those skilled in the art, the present invention will be further described below with reference to the accompanying drawings.
[0035] Figure 1 The Mg content of the ultrafiltration membranes for water treatment resistant to seawater corrosion in Examples 1-3 and Comparative Examples 1-4 of this invention before and after seawater immersion. 2+ Schematic diagram of removal rate test results;
[0036] Figure 2 The Ca2+ of the seawater-resistant ultrafiltration membranes for water treatment in Examples 1-3 and Comparative Examples 1-4 of this invention before and after seawater immersion. 2+ Schematic diagram of removal rate test results;
[0037] Figure 3 SO42-resistant ultrafiltration membranes for water treatment in Examples 1-3 and Comparative Examples 1-4 of this invention were tested before and after seawater immersion. 2- Schematic diagram of removal rate test results;
[0038] Figure 4 CI of the seawater-resistant ultrafiltration membranes for water treatment in Examples 1-3 and Comparative Examples 1-4 of this invention before and after seawater immersion. - Schematic diagram of removal rate test results;
[0039] Figure 5 This is a schematic diagram showing the test results of the antibacterial rate of Escherichia coli in the ultrafiltration membranes for water treatment resistant to seawater corrosion in Examples 1-3 and Comparative Examples 1-4 of the present invention before and after seawater immersion.
[0040] Figure 6 This is a schematic diagram showing the test results of the antibacterial rate of the ultrafiltration membranes for water treatment resistant to seawater corrosion in Examples 1-3 and Comparative Examples 1-4 of the present invention before and after immersion in seawater to Staphylococcus aureus. Detailed Implementation
[0041] To enable those skilled in the art to better understand the present invention, the technical solutions of the present invention will be clearly and completely described below with reference to the accompanying drawings of the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0042] Example 1:
[0043] This embodiment describes a method for preparing a seawater-resistant ultrafiltration membrane for water treatment, comprising the following steps:
[0044] Step S1: 10 mmol bisphenol AF, 20 mmol 4,4'-difluorodiphenyl sulfone, 10 mmol phenolphthalein, 25 mmol anhydrous potassium carbonate, 20 mL xylene and 50 mL sulfolane were added to a three-necked flask equipped with a stirrer, thermometer, gas delivery tube and reflux condenser. Nitrogen gas was introduced for protection. The mixture was stirred at 20 °C and 200 r / min for 10 min. The temperature was then raised to 120 °C and stirred for 3 h. The temperature was then raised to 160 °C and stirred for 5 h. After the reaction was completed, the reaction product was cooled to room temperature and poured into deionized water. The pH was then adjusted to 6 with 10% hydrochloric acid solution. The mixture was allowed to stand and then vacuum filtered. The filter cake was washed twice with anhydrous ethanol and distilled water. It was then placed in a vacuum drying oven and dried at 60 °C for 10 h to obtain carboxyl-containing fluorinated polyarylene ether sulfone material.
[0045] Step S2: 5g of 2-bromomethyl terephthalate, 25mL of 30% trimethylamine solution, and 40mL of anhydrous acetonitrile were added to a three-necked flask equipped with a stirrer, thermometer, gas delivery tube, and reflux condenser. Nitrogen gas was introduced for protection, and the mixture was stirred at 20℃ and 200r / min for 20min. Then, the mixture was heated to reflux and stirred for another 20h. After the reaction was completed, the product was cooled to room temperature, and the solvent was removed by rotary evaporation. The product was then purified by silica gel column chromatography using a mixed solvent of dichloromethane and anhydrous methanol in a volume ratio of 10:1 to obtain the quaternized dimethyl terephthalate compound.
[0046] Step S3: 3g of quaternized dimethyl terephthalate compound, 30mL of 3mol / L sodium hydroxide solution, 20mL of anhydrous methanol, and 10mL of anhydrous tetrahydrofuran were added to a three-necked flask equipped with a stirrer and a thermometer. The mixture was stirred at 20℃ and 200r / min for 3min. Then, the temperature was raised to 100℃ and the mixture was stirred for 10h. After the reaction was completed, the reaction product was cooled to room temperature, and the solvent was removed by rotary evaporation. The product was then poured into distilled water and the pH was adjusted to 3 with 25% hydrochloric acid solution. The product was then vacuum filtered, and the filter cake was placed in a vacuum drying oven and dried at 40℃ for 3h to obtain the quaternized dimethyl terephthalate compound.
[0047] Step S4: 10 mmol of quaternized terephthalic acid compound, 10 mmol of zinc nitrate, 20 mL of 30% hydrochloric acid solution and 50 mL of N,N-dimethylformamide were added to a three-necked flask equipped with a stirrer and a thermometer. The mixture was stirred at 20 °C and 200 r / min for 10 min. The temperature was then raised to 90 °C and the mixture was stirred for 24 h. After the reaction was completed, the reaction product was cooled to room temperature and centrifuged. The precipitate was soaked in anhydrous methanol for 24 h and then centrifuged again. The precipitate was placed in a vacuum drying oven and dried at 40 °C for 6 h to obtain the quaternized zinc-based metal-organic framework material.
[0048] Step S5: Add 3g of molybdenum disulfide nanoparticles with an average particle size of 200nm, 0.04g of polyvinylpyrrolidone PVP-K30, and 50mL of deionized water to a three-necked flask equipped with a stirrer and a thermometer. Sonicate the mixture at a frequency of 40kHz for 20min. Then, stir the mixture at 20℃ and a stirring rate of 200r / min for 10min. After that, add 0.6g of pyrrole and 3g of ferric chloride and continue stirring the mixture at 40℃ for 3h. After the reaction is complete, cool the reaction product to room temperature, centrifuge it, wash the precipitate twice with a 40% ethanol solution, and then place it in a vacuum drying oven and dry it at 60℃ for 3h to obtain modified molybdenum disulfide nanoparticles.
[0049] Step S6: Weigh out 17 parts by weight of carboxyl-containing fluorinated polyarylether sulfone material, 2 parts by weight of quaternized zinc-based metal-organic framework material, 0.8 parts by weight of modified nano-molybdenum disulfide powder, 0.5 parts by weight of carboxylated carbon nanotubes, 1 part by weight of polyvinylpyrrolidone, 0.5 parts by weight of polyethylene glycol, 2 parts by weight of crosslinking agent, 0.3 parts by weight of sodium dodecyl sulfate, and 80 parts by weight of N,N-dimethylacetamide, and set aside for later use; the carboxylated carbon nanotubes are high-purity multi-walled carbon nanotubes TNMC1; the polyvinylpyrrolidone is PVP-K30; the polyethylene glycol is PEG-6000; the crosslinking agent is silane coupling agent KH-560;
[0050] Step S7: Add carboxyl-containing fluorinated polyarylether sulfone material, quaternized zinc-based metal-organic framework material, modified nano-molybdenum disulfide powder, carboxylated carbon nanotubes, polyvinylpyrrolidone, polyethylene glycol, crosslinking agent, sodium dodecyl sulfate, and N,N-dimethylacetamide to a mixer. Stir and mix for 20 min at 20℃ and 500 r / min. Then, heat to 70℃ and continue stirring and mixing for 5 h. After standing for 2 h, pour the mixture onto a smooth glass plate and scrape it into a membrane with a thickness of 200 μm using a membrane scraper. After standing for 2 min, immerse the membrane in deionized water for 24 h to obtain an ultrafiltration membrane for water treatment that is resistant to seawater corrosion.
[0051] Example 2:
[0052] This embodiment describes a method for preparing a seawater-resistant ultrafiltration membrane for water treatment, comprising the following steps:
[0053] Step S1: 10 mmol bisphenol AF, 20 mmol 4,4'-difluorodiphenyl sulfone, 10 mmol phenolphthalein, 28 mmol anhydrous potassium carbonate, 22 mL xylene, and 52 mL sulfolane were added to a three-necked flask equipped with a stirrer, thermometer, gas delivery tube, and reflux condenser. Nitrogen gas was introduced for protection. The mixture was stirred at 22°C and 250 r / min for 15 min. The temperature was then raised to 125°C and the mixture was stirred for 3.5 h. The temperature was then raised to 170°C and the mixture was stirred for 5.5 h. After the reaction was completed, the reaction product was cooled to room temperature and poured into deionized water. The pH was then adjusted to 5.5 with 12% hydrochloric acid solution. The mixture was allowed to stand and then vacuum filtered. The filter cake was washed twice with anhydrous ethanol and distilled water, and then placed in a vacuum drying oven and dried at 65°C for 11 h to obtain a carboxyl-containing fluorinated polyarylene ether sulfone material.
[0054] Step S2: 5g of 2-bromomethyl terephthalate, 28mL of 32% trimethylamine solution, and 45mL of anhydrous acetonitrile were added to a three-necked flask equipped with a stirrer, thermometer, gas delivery tube, and reflux condenser. Nitrogen gas was introduced for protection, and the mixture was stirred at 22℃ and 250r / min for 25min. Then, the mixture was heated to reflux and stirred for another 25h. After the reaction was completed, the product was cooled to room temperature, and the solvent was removed by rotary evaporation. The product was then purified by silica gel column chromatography using a mixed solvent of dichloromethane and anhydrous methanol in a volume ratio of 11:1 to obtain the quaternized dimethyl terephthalate compound.
[0055] Step S3: 3g of quaternized dimethyl terephthalate compound, 35mL of sodium hydroxide solution with a molar concentration of 4mol / L, 25mL of anhydrous methanol, and 12mL of anhydrous tetrahydrofuran were added to a three-necked flask equipped with a stirrer and a thermometer. The mixture was stirred at 22℃ and a stirring rate of 250r / min for 4min. Then, the temperature was raised to 105℃ and the stirring was continued for 11h. After the reaction was completed, the reaction product was cooled to room temperature, and the solvent was removed by rotary evaporation. The product was then poured into distilled water and the pH was adjusted to 2.5 with 28% hydrochloric acid solution. The product was then vacuum filtered, and the filter cake was placed in a vacuum drying oven and dried at 42℃ for 4h to obtain the quaternized dimethyl terephthalate compound.
[0056] Step S4: 10 mmol of quaternized terephthalic acid compound, 10 mmol of zinc nitrate, 22 mL of 32% hydrochloric acid solution and 55 mL of N,N-dimethylformamide were added to a three-necked flask equipped with a stirrer and a thermometer. The mixture was stirred at 22 °C and 250 r / min for 15 min. The temperature was then raised to 95 °C and the mixture was stirred for 36 h. After the reaction was completed, the reaction product was cooled to room temperature and centrifuged. The precipitate was soaked in anhydrous methanol for 36 h and then centrifuged again. The precipitate was placed in a vacuum drying oven and dried at 42 °C for 7 h to obtain the quaternized zinc-based metal-organic framework material.
[0057] Step S5: Add 3g of molybdenum disulfide nanoparticles with an average particle size of 200nm, 0.06g of polyvinylpyrrolidone PVP-K30, and 52mL of deionized water to a three-necked flask equipped with a stirrer and a thermometer. Sonicate the mixture at a frequency of 45kHz for 25min. Then, stir the mixture at a temperature of 22℃ and a stirring rate of 250r / min for 15min. After that, add 0.9g of pyrrole and 4g of ferric chloride and continue stirring the mixture at a temperature of 42℃ for 4h. After the reaction is complete, cool the reaction product to room temperature, centrifuge it, wash the precipitate twice with a 45% ethanol solution, and then place it in a vacuum drying oven and dry it at a temperature of 65℃ for 4h to obtain modified molybdenum disulfide nanoparticles.
[0058] Step S6: Weigh out 21 parts by weight of carboxyl-containing fluorinated polyarylether sulfone material, 5 parts by weight of quaternized zinc-based metal-organic framework material, 2.2 parts by weight of modified nano-molybdenum disulfide powder, 1.1 parts by weight of carboxylated carbon nanotubes, 1.5 parts by weight of polyvinylpyrrolidone, 0.6 parts by weight of polyethylene glycol, 3 parts by weight of crosslinking agent, 0.4 parts by weight of sodium dodecyl sulfate, and 82 parts by weight of N,N-dimethylacetamide, and set aside for later use; the carboxylated carbon nanotubes are high-purity multi-walled carbon nanotubes TNMC1; the polyvinylpyrrolidone is PVP-K30; the polyethylene glycol is PEG-6000; the crosslinking agent is silane coupling agent KH-560;
[0059] Step S7: Add carboxyl-containing fluorinated polyarylether sulfone material, quaternized zinc-based metal-organic framework material, modified nano-molybdenum disulfide powder, carboxylated carbon nanotubes, polyvinylpyrrolidone, polyethylene glycol, crosslinking agent, sodium dodecyl sulfate, and N,N-dimethylacetamide to a mixer. Stir and mix for 25 min at 22°C and 600 r / min. Then, heat to 75°C and continue stirring and mixing for 5.5 h. After standing for 3 h, pour the mixture onto a smooth glass plate and scrape it into a membrane with a thickness of 200 μm using a membrane scraper. After standing for 2.5 min, immerse it in deionized water for 48 h to obtain an ultrafiltration membrane for water treatment that is resistant to seawater corrosion.
[0060] Example 3:
[0061] This embodiment describes a method for preparing a seawater-resistant ultrafiltration membrane for water treatment, comprising the following steps:
[0062] Step S1: 10 mmol bisphenol AF, 20 mmol 4,4'-difluorodiphenyl sulfone, 10 mmol phenolphthalein, 30 mmol anhydrous potassium carbonate, 25 mL xylene, and 55 mL sulfolane were added to a three-necked flask equipped with a stirrer, thermometer, gas delivery tube, and reflux condenser. Nitrogen gas was introduced for protection, and the mixture was stirred at 25°C and 300 r / min for 20 min. The temperature was then raised to 130°C and the mixture was stirred for 4 h. The temperature was then raised to 180°C and the mixture was stirred for 6 h. After the reaction was completed, the reaction product was cooled to room temperature and poured into deionized water. The pH was then adjusted to 5 with 15% hydrochloric acid solution and allowed to stand. The mixture was then vacuum filtered, and the filter cake was washed three times with anhydrous ethanol and distilled water. The filter cake was then placed in a vacuum drying oven and dried at 70°C for 12 h to obtain a carboxyl-containing fluorinated polyarylene ether sulfone material.
[0063] Step S2: 5g of 2-bromomethyl terephthalate, 30mL of 33% trimethylamine solution, and 50mL of anhydrous acetonitrile were added to a three-necked flask equipped with a stirrer, thermometer, gas delivery tube, and reflux condenser. Nitrogen gas was introduced for protection, and the mixture was stirred at 25℃ and 300r / min for 30min. Then, the mixture was heated to reflux and stirred for another 30h. After the reaction was completed, the product was cooled to room temperature, and the solvent was removed by rotary evaporation. The product was then purified by silica gel column chromatography using a mixed solvent of dichloromethane and anhydrous methanol in a volume ratio of 12:1 to obtain the quaternized dimethyl terephthalate compound.
[0064] Step S3: 3g of quaternized dimethyl terephthalate compound, 40mL of 5mol / L sodium hydroxide solution, 30mL of anhydrous methanol, and 15mL of anhydrous tetrahydrofuran were added to a three-necked flask equipped with a stirrer and a thermometer. The mixture was stirred at 25℃ and 300r / min for 5min. Then, the temperature was raised to 110℃ and the mixture was stirred for 12h. After the reaction was completed, the reaction product was cooled to room temperature, and the solvent was removed by rotary evaporation. The product was then poured into distilled water and the pH was adjusted to 2 with 30% hydrochloric acid solution. The product was then vacuum filtered, and the filter cake was placed in a vacuum drying oven and dried at 45℃ for 5h to obtain the quaternized dimethyl terephthalate compound.
[0065] Step S4: 10 mmol of quaternized terephthalic acid compound, 10 mmol of zinc nitrate, 25 mL of 35% hydrochloric acid solution and 60 mL of N,N-dimethylformamide were added to a three-necked flask equipped with a stirrer and thermometer. The mixture was stirred at 25 °C and 300 r / min for 20 min. Then, the temperature was raised to 100 °C and the mixture was stirred for 48 h. After the reaction was completed, the reaction product was cooled to room temperature and centrifuged. The precipitate was soaked in anhydrous methanol for 48 h and then centrifuged again. The precipitate was placed in a vacuum drying oven and dried at 45 °C for 8 h to obtain the quaternized zinc-based metal-organic framework material.
[0066] Step S5: Add 3g of molybdenum disulfide nanoparticles with an average particle size of 200nm, 0.08g of polyvinylpyrrolidone PVP-K30, and 55mL of deionized water to a three-necked flask equipped with a stirrer and a thermometer. Sonicate the mixture at a frequency of 50kHz for 30min. Then, stir the mixture at 25℃ and a stirring rate of 300r / min for 20min. After that, add 1.2g of pyrrole and 5g of ferric chloride and continue stirring the mixture at 45℃ for 5h. After the reaction is complete, cool the reaction product to room temperature, centrifuge it, wash the precipitate three times with a 50% ethanol solution, and then place it in a vacuum drying oven and dry it at 70℃ for 5h to obtain modified molybdenum disulfide nanoparticles.
[0067] Step S6: Weigh out 25 parts by weight of carboxyl-containing fluorinated polyarylether sulfone material, 8 parts by weight of quaternized zinc-based metal-organic framework material, 3.6 parts by weight of modified nano-molybdenum disulfide powder, 1.7 parts by weight of carboxylated carbon nanotubes, 2 parts by weight of polyvinylpyrrolidone, 0.7 parts by weight of polyethylene glycol, 4 parts by weight of crosslinking agent, 0.5 parts by weight of sodium dodecyl sulfate, and 85 parts by weight of N,N-dimethylacetamide, and set aside for later use; the carboxylated carbon nanotubes are high-purity multi-walled carbon nanotubes TNMC1; the polyvinylpyrrolidone is PVP-K30; the polyethylene glycol is PEG-6000; the crosslinking agent is silane coupling agent KH-560;
[0068] Step S7: Add carboxyl-containing fluorinated polyarylether sulfone material, quaternized zinc-based metal-organic framework material, modified nano-molybdenum disulfide powder, carboxylated carbon nanotubes, polyvinylpyrrolidone, polyethylene glycol, crosslinking agent, sodium dodecyl sulfate, and N,N-dimethylacetamide to a mixer. Stir and mix for 30 min at 25°C and 700 r / min. Then, heat to 80°C and continue stirring and mixing for 6 h. After standing for 4 h, pour the mixture onto a smooth glass plate and scrape it into a membrane with a thickness of 200 μm using a membrane scraper. After standing for 3 min, immerse it in deionized water for 72 h to obtain an ultrafiltration membrane for water treatment that is resistant to seawater corrosion.
[0069] Comparative Example 1:
[0070] This comparative example illustrates a method for preparing a seawater-resistant ultrafiltration membrane for water treatment, comprising the following steps:
[0071] Step S1: 10 mmol bisphenol AF, 20 mmol 4,4'-difluorodiphenyl sulfone, 10 mmol phenolphthalein, 30 mmol anhydrous potassium carbonate, 25 mL xylene, and 55 mL sulfolane were added to a three-necked flask equipped with a stirrer, thermometer, gas delivery tube, and reflux condenser. Nitrogen gas was introduced for protection, and the mixture was stirred at 25°C and 300 r / min for 20 min. The temperature was then raised to 130°C and the mixture was stirred for 4 h. The temperature was then raised to 180°C and the mixture was stirred for 6 h. After the reaction was completed, the reaction product was cooled to room temperature and poured into deionized water. The pH was then adjusted to 5 with 15% hydrochloric acid solution and allowed to stand. The mixture was then vacuum filtered, and the filter cake was washed three times with anhydrous ethanol and distilled water. The filter cake was then placed in a vacuum drying oven and dried at 70°C for 12 h to obtain a carboxyl-containing fluorinated polyarylene ether sulfone material.
[0072] Step S2: Weigh out 25 parts by weight of carboxyl-containing fluorinated polyarylene ether sulfone material, 1.7 parts by weight of carboxylated carbon nanotubes, 2 parts by weight of polyvinylpyrrolidone, 0.7 parts by weight of polyethylene glycol, 4 parts by weight of crosslinking agent, 0.5 parts by weight of sodium dodecyl sulfate, and 85 parts by weight of N,N-dimethylacetamide, and set aside for later use; the carboxylated carbon nanotubes are high-purity multi-walled carbon nanotubes TNMC1; the polyvinylpyrrolidone is PVP-K30; the polyethylene glycol is PEG-6000; and the crosslinking agent is silane coupling agent KH-560;
[0073] Step S3: Add carboxyl-containing fluorinated polyarylether sulfone material, carboxylated carbon nanotubes, polyvinylpyrrolidone, polyethylene glycol, crosslinking agent, sodium dodecyl sulfate, and N,N-dimethylacetamide to a mixer and stir for 30 minutes at 25°C and 700 r / min. Then, heat to 80°C and continue stirring for 6 hours. After standing for 4 hours, pour the mixture onto a smooth glass plate and scrape it into a membrane with a thickness of 200 μm using a membrane scraper. After standing for 3 minutes, immerse the membrane in deionized water for 72 hours to obtain an ultrafiltration membrane for water treatment that is resistant to seawater corrosion.
[0074] Comparative Example 2:
[0075] This comparative example illustrates a method for preparing a seawater-resistant ultrafiltration membrane for water treatment, comprising the following steps:
[0076] Step S1: 10 mmol bisphenol AF, 20 mmol 4,4'-difluorodiphenyl sulfone, 10 mmol phenolphthalein, 30 mmol anhydrous potassium carbonate, 25 mL xylene, and 55 mL sulfolane were added to a three-necked flask equipped with a stirrer, thermometer, gas delivery tube, and reflux condenser. Nitrogen gas was introduced for protection, and the mixture was stirred at 25°C and 300 r / min for 20 min. The temperature was then raised to 130°C and the mixture was stirred for 4 h. The temperature was then raised to 180°C and the mixture was stirred for 6 h. After the reaction was completed, the reaction product was cooled to room temperature and poured into deionized water. The pH was then adjusted to 5 with 15% hydrochloric acid solution and allowed to stand. The mixture was then vacuum filtered, and the filter cake was washed three times with anhydrous ethanol and distilled water. The filter cake was then placed in a vacuum drying oven and dried at 70°C for 12 h to obtain a carboxyl-containing fluorinated polyarylene ether sulfone material.
[0077] Step S2: 5g of 2-bromomethyl terephthalate, 30mL of 33% trimethylamine solution, and 50mL of anhydrous acetonitrile were added to a three-necked flask equipped with a stirrer, thermometer, gas delivery tube, and reflux condenser. Nitrogen gas was introduced for protection, and the mixture was stirred at 25℃ and 300r / min for 30min. Then, the mixture was heated to reflux and stirred for another 30h. After the reaction was completed, the product was cooled to room temperature, and the solvent was removed by rotary evaporation. The product was then purified by silica gel column chromatography using a mixed solvent of dichloromethane and anhydrous methanol in a volume ratio of 12:1 to obtain the quaternized dimethyl terephthalate compound.
[0078] Step S3: 3g of quaternized dimethyl terephthalate compound, 40mL of 5mol / L sodium hydroxide solution, 30mL of anhydrous methanol, and 15mL of anhydrous tetrahydrofuran were added to a three-necked flask equipped with a stirrer and a thermometer. The mixture was stirred at 25℃ and 300r / min for 5min. Then, the temperature was raised to 110℃ and the mixture was stirred for 12h. After the reaction was completed, the reaction product was cooled to room temperature, and the solvent was removed by rotary evaporation. The product was then poured into distilled water and the pH was adjusted to 2 with 30% hydrochloric acid solution. The product was then vacuum filtered, and the filter cake was placed in a vacuum drying oven and dried at 45℃ for 5h to obtain the quaternized dimethyl terephthalate compound.
[0079] Step S4: 10 mmol of quaternized terephthalic acid compound, 10 mmol of zinc nitrate, 25 mL of 35% hydrochloric acid solution and 60 mL of N,N-dimethylformamide were added to a three-necked flask equipped with a stirrer and thermometer. The mixture was stirred at 25 °C and 300 r / min for 20 min. Then, the temperature was raised to 100 °C and the mixture was stirred for 48 h. After the reaction was completed, the reaction product was cooled to room temperature and centrifuged. The precipitate was soaked in anhydrous methanol for 48 h and then centrifuged again. The precipitate was placed in a vacuum drying oven and dried at 45 °C for 8 h to obtain the quaternized zinc-based metal-organic framework material.
[0080] Step S5: Weigh out 25 parts by weight of carboxyl-containing fluorinated polyarylene ether sulfone material, 1.7 parts by weight of carboxylated carbon nanotubes, 8 parts by weight of quaternized zinc-based metal-organic framework material, 2 parts by weight of polyvinylpyrrolidone, 0.7 parts by weight of polyethylene glycol, 4 parts by weight of crosslinking agent, 0.5 parts by weight of sodium dodecyl sulfate, and 85 parts by weight of N,N-dimethylacetamide, and set aside for later use; the carboxylated carbon nanotubes are high-purity multi-walled carbon nanotubes TNMC1; the polyvinylpyrrolidone is PVP-K30; the polyethylene glycol is PEG-6000; the crosslinking agent is silane coupling agent KH-560;
[0081] Step S6: Add carboxyl-containing fluorinated polyarylether sulfone material, quaternized zinc-based metal-organic framework material, carboxylated carbon nanotubes, polyvinylpyrrolidone, polyethylene glycol, crosslinking agent, sodium dodecyl sulfate, and N,N-dimethylacetamide to a mixer. Stir and mix for 30 min at 25°C and 700 r / min. Then, heat to 80°C and continue stirring and mixing for 6 h. After standing for 4 h, pour the mixture onto a smooth glass plate and scrape it into a membrane with a thickness of 200 μm using a membrane scraper. After standing for 3 min, immerse it in deionized water for 72 h to obtain an ultrafiltration membrane for water treatment that is resistant to seawater corrosion.
[0082] Comparative Example 3:
[0083] This comparative example illustrates a method for preparing a seawater-resistant ultrafiltration membrane for water treatment, comprising the following steps:
[0084] Step S1: 10 mmol bisphenol AF, 20 mmol 4,4'-difluorodiphenyl sulfone, 10 mmol phenolphthalein, 30 mmol anhydrous potassium carbonate, 25 mL xylene, and 55 mL sulfolane were added to a three-necked flask equipped with a stirrer, thermometer, gas delivery tube, and reflux condenser. Nitrogen gas was introduced for protection, and the mixture was stirred at 25°C and 300 r / min for 20 min. The temperature was then raised to 130°C and the mixture was stirred for 4 h. The temperature was then raised to 180°C and the mixture was stirred for 6 h. After the reaction was completed, the reaction product was cooled to room temperature and poured into deionized water. The pH was then adjusted to 5 with 15% hydrochloric acid solution and allowed to stand. The mixture was then vacuum filtered, and the filter cake was washed three times with anhydrous ethanol and distilled water. The filter cake was then placed in a vacuum drying oven and dried at 70°C for 12 h to obtain a carboxyl-containing fluorinated polyarylene ether sulfone material.
[0085] Step S2: Add 3g of molybdenum disulfide nanoparticles with an average particle size of 200nm, 0.08g of polyvinylpyrrolidone PVP-K30, and 55mL of deionized water to a three-necked flask equipped with a stirrer and a thermometer. Sonicate the mixture at a frequency of 50kHz for 30min. Then, stir the mixture at 25℃ and a stirring rate of 300r / min for 20min. After that, add 1.2g of pyrrole and 5g of ferric chloride and continue stirring the mixture at 45℃ for 5h. After the reaction is complete, cool the reaction product to room temperature, centrifuge it, wash the precipitate three times with a 50% ethanol solution, and then place it in a vacuum drying oven and dry it at 70℃ for 5h to obtain modified molybdenum disulfide nanoparticles.
[0086] Step S3: Weigh out 25 parts by weight of carboxyl-containing fluorinated polyarylene ether sulfone material, 3.6 parts by weight of modified nano molybdenum disulfide powder, 1.7 parts by weight of carboxylated carbon nanotubes, 2 parts by weight of polyvinylpyrrolidone, 0.7 parts by weight of polyethylene glycol, 4 parts by weight of crosslinking agent, 0.5 parts by weight of sodium dodecyl sulfate, and 85 parts by weight of N,N-dimethylacetamide, and set aside for later use; the carboxylated carbon nanotubes are high-purity multi-walled carbon nanotubes TNMC1; the polyvinylpyrrolidone is PVP-K30; the polyethylene glycol is PEG-6000; the crosslinking agent is silane coupling agent KH-560;
[0087] Step S4: Add carboxyl-containing fluorinated polyarylene ether sulfone material, modified nano-molybdenum disulfide powder, carboxylated carbon nanotubes, polyvinylpyrrolidone, polyethylene glycol, crosslinking agent, sodium dodecyl sulfate, and N,N-dimethylacetamide to a mixer. Stir and mix for 30 min at 25°C and 700 r / min. Then, heat to 80°C and continue stirring and mixing for 6 h. After standing for 4 h, pour the mixture onto a smooth glass plate and scrape it into a membrane with a thickness of 200 μm using a membrane scraper. After standing for 3 min, immerse it in deionized water for 72 h to obtain an ultrafiltration membrane for water treatment that is resistant to seawater corrosion.
[0088] Comparative Example 4:
[0089] This comparative example illustrates a method for preparing a seawater-resistant ultrafiltration membrane for water treatment, comprising the following steps:
[0090] Step S1: 20 mmol bisphenol A, 20 mmol 4,4'-difluorodiphenyl sulfone, 30 mmol anhydrous potassium carbonate, 25 mL xylene, and 55 mL sulfolane were added to a three-necked flask equipped with a stirrer, thermometer, gas delivery tube, and reflux condenser. Nitrogen gas was introduced for protection, and the mixture was stirred at 25 °C and a stirring rate of 300 r / min for 20 min. The temperature was then raised to 130 °C and the stirring was continued for 4 h. The temperature was then raised to 180 °C and the stirring was continued for 6 h. After the reaction was completed, the reaction product was cooled to room temperature and then poured into deionized water. The pH was then adjusted to 5 with 15% hydrochloric acid solution and allowed to stand. The mixture was then vacuum filtered, and the filter cake was washed three times with anhydrous ethanol and distilled water. The filter cake was then placed in a vacuum drying oven and dried at 70 °C for 12 h to obtain polyarylene ether sulfone material.
[0091] Step S2: 10 mmol terephthalic acid, 10 mmol zinc nitrate, 25 mL 35% hydrochloric acid solution and 60 mL N,N-dimethylformamide were added to a three-necked flask equipped with a stirrer and thermometer. The mixture was stirred at 25 °C and 300 r / min for 20 min. Then the temperature was raised to 100 °C and the mixture was stirred for 48 h. After the reaction was completed, the reaction product was cooled to room temperature and centrifuged. The precipitate was soaked in anhydrous methanol for 48 h and then centrifuged again. The precipitate was placed in a vacuum drying oven and dried at 45 °C for 8 h to obtain a zinc-based metal-organic framework material.
[0092] Step S3: Weigh out 25 parts by weight of polyarylethersulfone material, 8 parts by weight of zinc-based metal-organic framework material, 3.6 parts by weight of molybdenum disulfide nanopowder, 1.7 parts by weight of carboxylated carbon nanotubes, 2 parts by weight of polyvinylpyrrolidone, 0.7 parts by weight of polyethylene glycol, 4 parts by weight of crosslinking agent, 0.5 parts by weight of sodium dodecyl sulfate, and 85 parts by weight of N,N-dimethylacetamide, and set aside. The average particle size of the molybdenum disulfide nanopowder is 200 nm; the carboxylated carbon nanotubes are high-purity multi-walled carbon nanotubes TNMC1; the polyvinylpyrrolidone is PVP-K30; the polyethylene glycol is PEG-6000; and the crosslinking agent is silane coupling agent KH-560.
[0093] Step S4: Add polyarylethersulfone material, zinc-based metal-organic framework material, nano-molybdenum disulfide powder, carboxylated carbon nanotubes, polyvinylpyrrolidone, polyethylene glycol, crosslinking agent, sodium dodecyl sulfate, and N,N-dimethylacetamide to a mixer and stir for 30 minutes at 25°C and 700 r / min. Then, heat to 80°C and continue stirring for 6 hours. After standing for 4 hours, pour the mixture onto a smooth glass plate and scrape it into a membrane with a thickness of 200 μm using a membrane scraper. After standing for 3 minutes, immerse the membrane in deionized water for 72 hours to obtain an ultrafiltration membrane for water treatment that is resistant to seawater corrosion.
[0094] Performance testing
[0095] The seawater corrosion-resistant ultrafiltration membranes for water treatment in Examples 1-3 and Comparative Examples 1-4 were tested for their removal performance and antibacterial performance before and after immersion in seawater for 60 days. The removal performance was measured under operating pressure of 1.0 MPa and a water recovery rate of 30% to determine the Mg content in seawater. 2+ Ca 2+ SO4 2- and CI - The removal rate, test results are as follows Figure 1-4 As shown, the antibacterial performance was tested using the traditional plate count method to determine the antibacterial rate against Escherichia coli and Staphylococcus aureus. The test results are as follows: Figure 5-6 As shown; among them, Mg in seawater 2+ Ca 2+ SO4 2- and CI - The mass concentrations were 1080, 351, 2366 and 15308 mg / L, respectively.
[0096] See Figure 1-6As shown, based on the comparison between Examples 1-3 and Comparative Examples 1-4, it can be seen that using carboxyl-containing fluorinated polyarylether sulfone material, and adding quaternary ammonium zinc-based metal-organic framework material and modified nano molybdenum disulfide powder can significantly improve the removal performance and antibacterial performance of ultrafiltration membrane, so that the ultrafiltration membrane for water treatment resistant to seawater corrosion of this application has excellent removal performance and antibacterial performance.
[0097] In the description of this specification, references to terms such as "an embodiment," "example," "specific example," etc., indicate that a specific feature, structure, material, or characteristic described in connection with that embodiment or example is included in at least one embodiment or example of the invention. In this specification, the illustrative expressions of the above terms do not necessarily refer to the same embodiment or example. Furthermore, the specific features, structures, materials, or characteristics described may be combined in any suitable manner in one or more embodiments or examples.
[0098] The above description is merely an example and illustration of the present invention. Those skilled in the art can make various modifications or additions to the specific embodiments described or use similar methods to replace them, as long as they do not deviate from the invention or exceed the scope defined in this application, they should all fall within the protection scope of the present invention.
Claims
1. A seawater-resistant ultrafiltration membrane for water treatment, characterized in that, Includes the following components by weight: The composition includes 17-25 parts of carboxyl-containing fluorinated polyarylether sulfone material, 2-8 parts of quaternized zinc-based metal-organic framework material, 0.8-3.6 parts of modified nano-molybdenum disulfide powder, 0.5-1.7 parts of carboxylated carbon nanotubes, 1-2 parts of polyvinylpyrrolidone, 0.5-0.7 parts of polyethylene glycol, 2-4 parts of crosslinking agent, 0.3-0.5 parts of sodium dodecyl sulfate, and 80-85 parts of N,N-dimethylacetamide. The carboxyl-containing fluorinated polyarylene sulfone material is prepared by the following steps: Bisphenol AF, 4,4'-difluorodiphenyl sulfone, phenolphthalein, anhydrous potassium carbonate, xylene, and sulfolane were added to a three-necked flask equipped with a stirrer, thermometer, gas delivery tube, and reflux condenser. Nitrogen gas was introduced for protection, and the mixture was stirred at 20-25℃ and 200-300 r / min for 10-20 min. The temperature was then raised to 120-130℃ and the stirring was continued for 3-4 h. The temperature was then raised to 160-180℃ and the stirring was continued for 5-6 h. After the reaction was completed, the product was cooled to room temperature and poured into deionized water. The pH was then adjusted to 5-6 with hydrochloric acid solution, and the mixture was allowed to stand. The mixture was then vacuum filtered, and the filter cake was washed 2-3 times with anhydrous ethanol and distilled water. The cake was then placed in a vacuum drying oven and dried at 60-70℃ for 10-12 h to obtain a carboxyl-containing fluorinated polyarylene ether sulfone material. The zinc quaternary ammonium-based metal-organic framework material is prepared by the following steps: Step A1: Dimethyl 2-bromomethyl terephthalate, trimethylamine solution, and anhydrous acetonitrile were added to a three-necked flask equipped with a stirrer, thermometer, gas delivery tube, and reflux condenser. Nitrogen gas was introduced for protection, and the reaction was stirred at 20-25℃ and 200-300 r / min for 20-30 min. Then, the temperature was raised to reflux and the reaction was stirred for another 20-30 h. After the reaction was completed, the reaction product was cooled to room temperature, and the solvent was removed by rotary evaporation. The product was then purified by silica gel column chromatography with a mixed solvent to obtain the quaternized dimethyl terephthalate compound. Step A2: Add the quaternized dimethyl terephthalate compound, sodium hydroxide solution, anhydrous methanol, and anhydrous tetrahydrofuran to a three-necked flask equipped with a stirrer and thermometer. Stir the reaction at 20-25℃ and 200-300 r / min for 3-5 min. Then, raise the temperature to 100-110℃ and continue stirring for 10-12 h. After the reaction is complete, cool the reaction product to room temperature, remove the solvent by rotary evaporation, pour it into distilled water, adjust the pH to 2-3 with hydrochloric acid solution, and then filter under vacuum. Place the filter cake in a vacuum drying oven and dry it at 40-45℃ for 3-5 h to obtain the quaternized dimethyl terephthalate compound. Step A3: Quaternized terephthalic acid compound, zinc nitrate, hydrochloric acid solution, and N,N-dimethylformamide are added to a three-necked flask equipped with a stirrer and thermometer. The mixture is stirred at 20-25℃ and 200-300 r / min for 10-20 min. Then, the temperature is raised to 90-100℃ and the mixture is stirred for 24-48 h. After the reaction is completed, the reaction product is cooled to room temperature and then centrifuged. The precipitate is soaked in anhydrous methanol for 24-48 h and then centrifuged again. The precipitate is placed in a vacuum drying oven and dried at 40-45℃ for 6-8 h to obtain quaternized zinc-based metal-organic framework material. The modified nano-molybdenum disulfide powder is prepared by the following steps: Nano-molybdenum disulfide powder, polyvinylpyrrolidone, and deionized water were added to a three-necked flask equipped with a stirrer and thermometer. The mixture was sonicated at a frequency of 40-50 kHz for 20-30 min. Then, the mixture was stirred at a temperature of 20-25℃ and a stirring rate of 200-300 r / min for 10-20 min. Pyrrole and ferric chloride were then added, and the mixture was heated to 40-45℃ and stirred for another 3-5 h. After the reaction was completed, the product was cooled to room temperature, centrifuged, and the precipitate was washed 2-3 times with ethanol solution. The precipitate was then placed in a vacuum drying oven and dried at a temperature of 60-70℃ for 3-5 h to obtain modified nano-molybdenum disulfide powder.
2. The ultrafiltration membrane for water treatment resistant to seawater corrosion according to claim 1, characterized in that, The ratio of bisphenol AF, 4,4'-difluorodiphenyl sulfone, phenolphthalein, anhydrous potassium carbonate, xylene, and sulfolane is 10 mmol: 20 mmol: 10 mmol: 25-30 mmol: 20-25 mL: 50-55 mL; the mass fraction of the hydrochloric acid solution is 10-15%.
3. The ultrafiltration membrane for water treatment resistant to seawater corrosion according to claim 1, characterized in that, In step A1, the ratio of dimethyl 2-bromomethyl terephthalate, trimethylamine solution, and anhydrous acetonitrile is 5g:25-30mL:40-50mL; the mass fraction of the trimethylamine solution is 30-33%; and the mixed solvent is a mixture of dichloromethane and anhydrous methanol in a volume ratio of 10-12:
1.
4. The ultrafiltration membrane for water treatment resistant to seawater corrosion according to claim 1, characterized in that, In step A2, the ratio of the quaternized dimethyl terephthalate compound, sodium hydroxide solution, anhydrous methanol, and anhydrous tetrahydrofuran is 3g:30-40mL:20-30mL:10-15mL; the molar concentration of the sodium hydroxide solution is 3-5mol / L; and the mass fraction of the hydrochloric acid solution is 25-30%.
5. The ultrafiltration membrane for water treatment resistant to seawater corrosion according to claim 1, characterized in that, In step A3, the ratio of the quaternized terephthalic acid compound, zinc nitrate, hydrochloric acid solution, and N,N-dimethylformamide is 10 mmol: 10 mmol: 20-25 mL: 50-60 mL; the mass fraction of the hydrochloric acid solution is 30-35%.
6. The ultrafiltration membrane for water treatment resistant to seawater corrosion according to claim 1, characterized in that, The ratio of the nano-molybdenum disulfide powder, polyvinylpyrrolidone, deionized water, pyrrole, and ferric chloride is 3g:0.04-0.08g:50-55mL:0.6-1.2g:3-5g; the average particle size of the nano-molybdenum disulfide powder is 200nm; and the polyvinylpyrrolidone is PVP-K30.
7. A method for preparing a seawater corrosion-resistant ultrafiltration membrane for water treatment as described in any one of claims 1-6, characterized in that, Includes the following steps: Step 1: Weigh out 17-25 parts by weight of carboxyl-containing fluorinated polyarylether sulfone material, 2-8 parts by weight of quaternized zinc-based metal-organic framework material, 0.8-3.6 parts by weight of modified nano molybdenum disulfide powder, 0.5-1.7 parts by weight of carboxylated carbon nanotubes, 1-2 parts by weight of polyvinylpyrrolidone, 0.5-0.7 parts by weight of polyethylene glycol, 2-4 parts by weight of crosslinking agent, 0.3-0.5 parts by weight of sodium dodecyl sulfate, and 80-85 parts by weight of N,N-dimethylacetamide, and set aside. Step 2: Add carboxyl-containing fluorinated polyarylether sulfone material, quaternized zinc-based metal-organic framework material, modified nano-molybdenum disulfide powder, carboxylated carbon nanotubes, polyvinylpyrrolidone, polyethylene glycol, crosslinking agent, sodium dodecyl sulfate, and N,N-dimethylacetamide to a mixer. Stir and mix for 20-30 minutes at a temperature of 20-25℃ and a stirring rate of 500-700 r / min. Then, raise the temperature to 70-80℃ and continue stirring and mixing for 5-6 hours. After standing for 2-4 hours, pour the mixture onto a smooth glass plate and scrape it with a membrane scraper to form a membrane with a thickness of 100-500 μm. After standing for 2-3 minutes, immerse it in deionized water for 24-72 hours to obtain an ultrafiltration membrane for water treatment that is resistant to seawater corrosion.
8. The method for preparing a seawater corrosion-resistant ultrafiltration membrane for water treatment according to claim 7, characterized in that, The carboxylated carbon nanotubes are high-purity multi-walled carbon nanotubes TNMC1; the polyvinylpyrrolidone is PVP-K30; the polyethylene glycol is PEG-6000; and the crosslinking agent is silane coupling agent KH-560.
Citation Information
Patent Citations
TiO2 / fluorine-containing polyether sulphone, preparation method and hybrid ultrafiltration membrane
CN105694458A
Magnetic quaternized ZIFs nanoparticle and modified ultrafiltration membrane thereof
CN119060354A